Serodiagnosis of swine pleuropneumonia due to Actinobacillus pleuropneumoniae serotypes 7 and 4 using long-chain lipopolysaccharides. - Gottschalk, M (1997)
A saline boiled extract (SBE), capsular polysaccharides (CPS) and long-chain lipopolysaccharides (LC-LPS) of Actinobacillus pleuropneumoniae serotype 7 have been evaluated in ELISA for the serodiagnosis of swine pleuropneumonia caused by this serotype. Mean optical densities (ODs) obtained with the 3 antigens using sera from negative herds as well as from animals experimentally and naturally exposed to A. pleuropneumoniae serotypes 7 or 4 were not statistically different. The positive ELISA reaction with anti-serotype 4 sera was unexpected with the CPS, which are supposed to be serotype-specific; LPS traces present in the CPS appeared to be responsible for this reaction. In addition, sera from animals exposed to A. pleuropneumoniae serotypes 5 or 10 presented cross-reactions with the SBE and the CPS, but not with the LC-LPS. Cross-reactions were mainly due to rough LPS, as shown by immunoblotting. The LC-LPS is easily obtainable and can be used for the detection of antibodies in animals infected with A. pleuropneumoniae serotypes 7 and 4.